Personality theories : critical perspectives - Ellis, Albert, 1913-2007.; Abrams, Mike.; Abrams, Lidia D. (Lidia Dengelegi) (Los Angeles : SAGE Publications, 2009)
"Personality Theories: Critical Perspectives is the groundbreaking, final text written by Albert Ellis, long considered the grandfather of cognitive behavioral therapies. The book provides students with supporting and contradictory evidence for the development of personality theories through time. Without condemning the founding theorists who came before him, Ellis builds on more than a century of psychological research to re-examine the theories of Freud, Jung, and Adler while taking an equally critical look at modern, research-based theories, including his own." "This enlightening text will provide insight into personality theory for graduate-level students and clinicians who have not had undergraduate psychology. It should be required reading for upper-level and graduate courses in psychology, counseling, and social work."--BOOK JACKET.
1. The Study of Personality: Introduction -- 2. Historical Perspectives on Personality -- 3. Personality Research -- 4. Freud and the Dynamic Unconscious -- 5. Psychoanalysis in Theory and Practice -- 6. Freud's Followers -- 7. Psychiatric and Medical Models -- 8. The Neo-Freudians -- 9. Personality and Traits -- 10. Behaviorist Views of Personality -- 11. Humanistic Views of Personality -- 12. Carl Rogers and Humanist Psychotherapy -- 13. Early Cognitive Views of Personality -- 14. Biology, Genetics, and the Evolution of Personality -- 15. Abnormal Personality and Personality Disorders -- 16. Albert Ellis and the Rational Emotive Behavioral Theory of Personality -- 17. Religious, New Age, and Traditional Approaches to Personality.
Includes bibliographical references (p. 627-669) and index.
Keywords: Personality